2017
DOI: 10.1111/iep.12226
|View full text |Cite
|
Sign up to set email alerts
|

Low‐level laser therapy (780 nm) combined with collagen sponge scaffold promotes repair of rat cranial critical‐size defects and increases TGF‐β, FGF‐2, OPG/RANK and osteocalcin expression

Abstract: The aim of this study was to evaluate the effect of collagen sponge scaffold (CSS) implantation associated with low-level laser therapy (LLLT) on repairing bone defects. A single 5-mm cranial defect was surgically created in forty Wistar rats, which then received one of the following four interventions (n = 10 per group): no treatment (G0); bone defect implanted with collagen sponge scaffold (CSS) alone (G1); defect treated with low-level laser therapy (LLLT) (wavelength 780 nm; total energy density 120 J/cm ;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 50 publications
2
9
0
Order By: Relevance
“…The defects filled with fibrin and xenograft (FSB and FSB PBMT ) sealers showed intense angiogenesis as early as 14 days, as well as the presence of reactional tissue at 42 days of resolution [36]. The tissue reaction observed in these groups did not trigger a foreign body type granulomatous reaction, which suggests that the grafts used were biocompatible [26,37,38] and the biological response was consistent with the inflammatory process after implantation of the biomaterial [14,35,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The defects filled with fibrin and xenograft (FSB and FSB PBMT ) sealers showed intense angiogenesis as early as 14 days, as well as the presence of reactional tissue at 42 days of resolution [36]. The tissue reaction observed in these groups did not trigger a foreign body type granulomatous reaction, which suggests that the grafts used were biocompatible [26,37,38] and the biological response was consistent with the inflammatory process after implantation of the biomaterial [14,35,39,40,41,42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Other attempts have been studied to minimise the time of bone healing and to reduce the chance of possible complications arising from the abnormal regeneration process. Among them, low-intensity pulsed ultrasound [12] and laser photobiomodulation therapy have been highlighted by their satisfactory effects on bone metabolism and repair, due to their possible osteogenic effect [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Although through different methodologies and with different cell lines, in general, PBM upregulates FGF-2 synthesis [19,20,36,37], similarly to the result of this study.…”
Section: -Intergroup Comparisonsupporting
confidence: 82%
“…Other studies have also demonstrated that LPLI affects osteogenesis and bone repair in comparative animal models [23][24][25][26][27][28]. LPLI therapies also induce alkaline phosphatase activity and increase osteocalcin gene expression, thus contributing to bone formation [29][30][31].…”
Section: Introductionmentioning
confidence: 96%